Consideration of workers’ opinion in the decision-making process in the RMG Sector: Evidence from Bangladesh - Hawlader, Md. Rasel; Rana , Md. Masud; Kalam, Abul; Polas, Mohammad Rashed Hasan (Goodwood Publishing, 2021)
Purpose: This study investigated the relationship between workers' perspectives on career development programs, remuneration packages, and their involvement in Readymade Garment (RMG) sector policymaking. Research methodology: Using a well-structured questionnaire, 226 people from a variety of industries were surveyed. Statistical software SPSS was used to examine the data and test the hypotheses that were put forth in the study. Using a conceptual framework, the study examines the relationship between the independent variables, such as the career development program and remuneration package, and the dependent variable, worker perception. Results: The findings of the study reveal that there is a significant positive relationship between workers’ opinions regarding career development programs and participation in the decision-making process. The study also identifies that there is a significant positive relationship between workers’ opinions regarding compensation packages as well as participation in the decision-making process of RMG sector in Bangladesh. In addition, workers’ participation has a significant impact on the decision-making process of the organization. Limitations: Two hundred and twenty-six samples from the primary source were used in this investigation. Having additional samples and secondary data would help researchers better understand the clothing industry as a whole. Contribution: The researchers believe that this study contributes to the current body of knowledge by underlining the importance of workers' opinions in the decision-making process in Bangladesh's RMG sector.